Hybrid Photocatalyst for Hydrogen Production: The Effect of Fluorine on Optoelectronic Properties of Conjugated Porous Polymers. (8th September 2022) - Gomez‐Mendoza, Miguel; Pintado‐Sierra, Mercedes; Monterde, Cristina; Barawi, Mariam; Sánchez, Félix; Iglesias, Marta; de la Peña O'Shea, Víctor A.; Liras, Marta
Abstract: Phenanthrenequinone (PhQ) based Conjugated Porous Polymers (CPPs) are synthetized without and with the presence of fluorine atoms in the trisubstituted core benzene unit (CPP‐FPA and CPP‐PA ). Furthermore, organic‐inorganic hybrid heterojunctions based on these CPPs and TiO2 as inorganic semiconductor are prepared (CPP‐FPA@T‐10 and CPP‐PA@T‐10, with the polymer loading ≈10 wt.%). The photonic efficiency for H2 photoproduction is 33% higher when the CPP has fluorine atoms. This enhancement is even higher in presence of 1 wt.% platinum as co‐catalyst. Thus, the Pt/CPP‐FPA@T‐10 hybrid (≈31.7 mmol g –1 h –1 and 11.7% of photonic efficiency) presents H2 production nearly twice than that of the nonfluorinated hybrid Pt/CPP‐PA@T‐10 (≈16.6 mmol g –1 h –1 and 6.1% of photonic efficiency) and 3.5‐times higher than that of the Pt/TiO2 (≈8.9 mmol g –1 h –1 and 3.29% of photonic efficiency) photocatalyst. Charge dynamics studies show that both hybrid heterojunctions exhibit a direct Z‐scheme charge transfer mechanism, and the presence of fluorine atoms in the CPP structure leads to an increasing charge separation lifetime which is in accordance with the better performance in H2 production. These findings on fluorine doping provide essential clues for the design of structure electronic engineered CPPs for energy conversion and storage technologies. Abstract : Conjugated Porous Polymers (CPPs) with fluorine atoms in the molecular structure stabilize their Highest Occupied Molecular Orbital. In hybrid with a Z‐scheme charge transfer, this effect is responsible for an incremental transient lifetime and an increase in the photocatalytic activity. Therefore, hybrids composed by a couple Phenanthrenequinone based CPPs and TiO2 are compared as photocatalyst in H2 production.